2011
DOI: 10.1007/s00167-011-1475-3
|View full text |Cite
|
Sign up to set email alerts
|

A matched pairs comparison of single- versus double-bundle anterior cruciate ligament reconstructions, clinical results and manual laxity testing

Abstract: DB ACL reconstruction appeared to more consistently result in significantly higher subjective outcome scores and manual tests of joint stability than SB ACL reconstruction. Besides the surgical technique, normal extension and quadriceps strength after surgery were identified to be an essential component in order to provide the patient with a successful outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 73 publications
0
33
0
3
Order By: Relevance
“…Desai et al 20 Zhu et al 12 Kongtharvonskul et al 19 Li et al 18 (2013) Xu et al 13 Tiamklang et al 15 van Eck et al 14 Meredick et al 16 Gobbi, 2012 28 þ þ À À À þ À À À Hussein, 2012 29 À þ À À þ þ À À À Lee, 2012 30 À þ À À þ À À À À Nuñez, 2012 31 À À À À þ À À À À Ochiai, 2012 32 À À À À þ À À À À Lee, 2012 33 þ À À À À À À À À Suomalainen, 2012 34 À þ À À À À À À À Araki, 2011 35 À þ þ þ þ þ þ À À Fujita, 2011 36 þ þ þ À À þ À À À Hemmerich, 2011 37 À þ þ À þ À À À À Kyoung, 2011 38 þ À À À À À À À À Misonoo, 2011 39 À þ À þ À À þ À À Plaweski, 2011 40 À þ À À À À À À À Siebold, 2011 41 þ À À À À À À À À Stefani, 2011 42 þ À À À À À À À À Suomalainen, 2011 43 þ…”
Section: Discussionunclassified
“…Desai et al 20 Zhu et al 12 Kongtharvonskul et al 19 Li et al 18 (2013) Xu et al 13 Tiamklang et al 15 van Eck et al 14 Meredick et al 16 Gobbi, 2012 28 þ þ À À À þ À À À Hussein, 2012 29 À þ À À þ þ À À À Lee, 2012 30 À þ À À þ À À À À Nuñez, 2012 31 À À À À þ À À À À Ochiai, 2012 32 À À À À þ À À À À Lee, 2012 33 þ À À À À À À À À Suomalainen, 2012 34 À þ À À À À À À À Araki, 2011 35 À þ þ þ þ þ þ À À Fujita, 2011 36 þ þ þ À À þ À À À Hemmerich, 2011 37 À þ þ À þ À À À À Kyoung, 2011 38 þ À À À À À À À À Misonoo, 2011 39 À þ À þ À À þ À À Plaweski, 2011 40 À þ À À À À À À À Siebold, 2011 41 þ À À À À À À À À Stefani, 2011 42 þ À À À À À À À À Suomalainen, 2011 43 þ…”
Section: Discussionunclassified
“…1-3 Therefore double-bundle ACL reconstruction is gaining popularity, and some studies have reported similar or superior results compared with single-bundle reconstruction. [4][5][6][7] These strategies are also supported by evidence showing that superior clinical outcomes occur when graft placement is aligned with the native ACL. 3,8,9 The transtibial drilling method has become widely accepted, and many studies have reported good results.…”
mentioning
confidence: 94%
“…3,9,22 Although numerous advances have been made in surgical reconstruction techniques and graft choices, it is well recognized that some patients continue to experience persistent rotatory knee instability after ACL reconstruction. 16,17,34,36 It has been suggested that failure to address additional secondary stabilizers may contribute to this postoperative instability. In fact, unaddressed meniscal tears, underappreciated meniscocapsular injuries, increased posterior tibial slope, and anterolateral capsular injuries have all been demonstrated to play a role in rotatory knee stability.…”
mentioning
confidence: 99%